Checklist "Open Access Policies": Analysis of the Open Access Policies of Public Universities in Austria - Bruno Bauer; Andreas Ferus; Lisa Schilhan (Mitteilungen der Vereinigung Österreichischer Bibliothekarinnen und Bibliothekare, 2016)
This checklist provides an overview of the Open Access policies implemented at Austrian universities and extramural research institutions. Furthermore, the polices adopted at nine public universities are analyzed and the respective text modules are categorized thematically. The second part of the checklist presents measures for the promotion of Open Access following the implementation of an Open Access policy.